A comprehensive comparison of different MPPT techniques for photovoltaic systems - Rezk, Hegazy; Eltamaly, Ali M. (Solar energy, 2015)
•The behavior of different MPPT techniques applied to PV systems.•Using co-simulation between PSIM and Simulink software packages.•Modeling and simulation of four PV MPPT techniques.•Transient and steady state response of four PV MPPT techniques. This paper aimed to study the behavior of different maximum power point tracking (MPPT) techniques applied to PV systems. In this work, techniques such as hill climbing (HC), incremental conductance (INC), perturb-and-observe (P&O), and fuzzy logic controller (FLC) are assessed. A model of PV module and DC/DC boost converter with the different techniques of MPPTs was simulated using PSIM and Simulink software. Co-simulation between PSIM and Simulink software packages is used to establish FLC MPPT technique. The co-simulation is done to take advantage of each program to handle certain part of the system. The response of the different MPPT techniques is evaluated in rapidly changing weather conditions. The results indicate that, FLC performed best among compared MPPT techniques followed by P&O, INC, and, HC MPPT techniques in both dynamic response and steady-state in most of the normal operating range.